Short-Term Education Abroad and Global Competence: Assessing Student Outcomes and Program Impact - Chieffo, Lisa P.; Ammigan, Ravichandran; Fan, Meng; Wei, Rujia; Shadowen, Noel L. (Journal of Interdisciplinary Studies in Education, 2026)
This study examines the impact of short-term education abroad programs on the global   competencies of 829 undergraduate students at a mid-sized public university. Students participated in three- to four-week international education programs during the winter of 2023 and were asked to complete pre- and post-program self-rated measures of their attitudes, knowledge, and awareness in the areas of cultural engagement, diversity tolerance, ambiguity tolerance, knowledge of the host site, and perceived resilience. Results showed that across the duration of their short-term experience abroad students reported increased competencies in all areas except for perceived resilience. The combination of host-country language and language of instruction (English or another language) minimally influenced results in a few areas, including ambiguity tolerance and diversity openness.